Study of physicochemical properties of hydrophobic calcite based on sugar factory defecates - Masharipova Sharofat; Jumaniyazov Maxsud; Turkmenbaeva Mayra; Kabulova Lola (E3S Web of Conferences)
This paper presents an innovative technology for producing hydrophobic calcite based on defecate, a by-product of sugar production. The stages of purification, mechanical activation and chemical modification of defecate using hydrophobizing agents, in particular, stearates and organosilicon compounds, are studied in detail. The results of the analysis of the structure, morphology and granulometric composition of the obtained material are presented. Particular attention is paid to the modification of the hydrophobic properties of calcite, carried out by standardized methods (GOST 30136-9). It was found that the obtained material is characterized by improved dispersibility in polymer matrices, which determines its potential as a filler for paints and varnishes, building mixtures and polymer composites. The studies confirmed the possibility of targeted modification of the properties of the obtained calcite by varying the synthesis conditions, which opens up new prospects for its practical application. Thus, the developed technology allows not only to efficiently utilize sugar production waste, but also to create valuable functional materials for various industries, promoting the development of environmentally friendly and resource-saving technologies.